Multipoint feedback : a 360 [degrees] catalyst for change - Jude-York, Deborah (Crisp Pub. Menlo ParkUS, 1997)
Examines multipoint feedback and its usefulness as a catalyst for change. Explains the mechanics of a multipoint feedback survey and discusses how to implement and evaluate it.